Insomnia Improved by Intravenous Mesenchymal Stem Cell Transplant: A Case Report - Pazili, Takahiro Honda (Sleep Science, 2025)
While several therapeutic options for insomnia are currently available, they often require long-term use and come with certain disadvantages. Given insomnia's significant impact on health overall, more effective treatments are warranted. Here, we report two patients with moderate to severe insomnia whose symptoms significantly improved following the intravenous administration of ex vivo-expanded bone marrow-derived mesenchymal stem cells (MSC).The cases were 50-year-old and 38-year-old men with mild diabetes. They both developed insomnia several years ago and suffered from it despite taking some medications. We cultured their bone-marrow-derived MSCs and intravenously administered 1,5 × 108 cells to each patient. After the treatment, the insomnia of both patients was drastically improved, while diabetes itself showed only mild improvement. Notably, their improvements were associated with an increase in plasma interleukin-4 levels. This is the first case report demonstrating the therapeutic effects of MSCs on insomnia.
Keywords: insomnia; mesenchymal stem cells; cell transplantation; interleukin-4